Chondrichthyans of the San Matías Gulf, Patagonia, Argentina - Perier, María Raquel (2011)
The San Matías Gulf (SMG; 41°- 42° S; 64°- 65° W) is the largest gulf in Northern Patagonia, Argentina.Up to date, the chondrichthyan fauna of this area has not been reported. Therefore, the aim of this work is to provide a list with species presence and biological characteristics of the chondrichthyans recorded in SMG during the last 30 years. A total of 13 sharks distributed in 11 families, 19 skates and rays distributed in six families, and one holocephalan have been so far recorded in SMG. From the zoogeographical point of view, this chondrichthyan fauna is a mixed assemblage of species typically found in the Argentinean and Magellanean Provinces. The holocephalan Callorhinchus callorynchus is the most landed chondricthyan of the local fishery. With it, five sharks and seven skates are also exploited.